Tryptophan Metabolites as Mediators of Microbiota-Gut-Brain Communication: Focus on Isatin - Medvedev, Alexei; Buneeva, Olga (Frontiers in Behavioral Neuroscience, 2022)
Isatin (indole-2,3-dione) is an endogenous regulator, exhibiting various behavioral, biological, and pharmacological activities. Synthesis of isatin includes several crucial stages: cleavage of the tryptophan side chain and subsequent oxidation of the indole nucleus. Although these stages require concerted action of bacterial and host enzymes, there are two pathways of isatin formation: the host and bacterial pathways. Isatin acts as a neuroprotector in different experimental models of neurodegeneration. Isatin effects are realized via up- and downregulation of isatin-responsive genes and via interaction with numerous isatin-binding proteins identified in the brain. The effect of isatin on protein-protein interactions in the brain may be important for realization of weak inhibition of multiple receptor targets.